The Use of Artificial Intelligence in Digital Marketing : A Qualitative Analysis of Small and Medium-Sized Companies in Azerbaijan - Farzaliyev, Siyavush (2025)
This study investigates how small and medium-sized enterprises (SMEs) in Azerbaijan integrate artificial intelligence (AI) into their digital marketing activities and how this transformation affects their strategies, operations, and customer relationships.The objectives of the study are to reveal how SMEs in Azerbaijan use artificial intelligence technologies in their digital marketing activities, what kind of changes these technologies cause in areas such as strategy, productivity, reaching the target audience, and what kind of ethical, technical or human challenges they encounter. Through semi-structured interviews with digital marketing managers of ten companies, the research explores the role of AI in personalization, content production, segmentation, and decision-making processes. The findings show that AI is not only used for automation but is seen as a collaborator that supports creativity and enhances efficiency. However, the study also reveals ethical concerns, technical challenges, and human limitations that accompany this transformation. The results emphasize that trust, transparency, and human control are essential elements in the adoption of AI in marketing. This research offers a grounded perspective on how AI changes not only tools but also the mindset and responsibility in modern marketing practices.